2017
DOI: 10.21873/anticanres.11682
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcome of Surgical Patients with Non-B Non-C Hepatocellular Carcinoma

Abstract: Surgical patients with NBNC-HCC often have concomitant DM, HTN and high BMI, for whom factors related to prognosis were Alb and AFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…of studies No. of patients RR/MD 95% CI a Test for overall effect Heterogeneity P P I 2 (%) Age (years) NBNC-HCC versus B-HCC 23 [ 9 11 , 14 , 15 , 21 25 , 28 30 , 32 , 33 , 35 40 , 43 , 46 ] 7830 10.04 8.55, 11.53 < 0.00001 < 0.00001 92 NBNC-HCC versus C-HCC 21 [ 9 11 , 14 , 15 , 21 25 , 28 30 , 32 , 33 , 35 37 , 39 , 40 , 43 ] 14,317 0.19 -1.12, 1.50 0.78 < 0.00001 93 NBNC-HCC versus BC-HCC 6 [ 9 , 11 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…of studies No. of patients RR/MD 95% CI a Test for overall effect Heterogeneity P P I 2 (%) Age (years) NBNC-HCC versus B-HCC 23 [ 9 11 , 14 , 15 , 21 25 , 28 30 , 32 , 33 , 35 40 , 43 , 46 ] 7830 10.04 8.55, 11.53 < 0.00001 < 0.00001 92 NBNC-HCC versus C-HCC 21 [ 9 11 , 14 , 15 , 21 25 , 28 30 , 32 , 33 , 35 37 , 39 , 40 , 43 ] 14,317 0.19 -1.12, 1.50 0.78 < 0.00001 93 NBNC-HCC versus BC-HCC 6 [ 9 , 11 ...…”
Section: Resultsmentioning
confidence: 99%
“…of studies No. of patients RR/MD a 95% CI Test for overall effect Heterogeneity P P I 2 (%) ALT (U/L) NBNC-HCC versus B-HCC 14 [ 9 , 11 , 14 , 22 , 24 , 25 , 29 , 32 , 33 , 38 , 39 , 43 , 45 ] 2126 -9.62 -14.08, -5.17 < 0.0001 < 0.0001 68 NBNC-HCC versus C-HCC 12 [ 9 , 11 , 14 , 22 , 24 , 25 , 29 , 32 , 33 , 39 , 40 , 43 ] 3100 -25.04 -34.95, -15.13 < 0.00001 < 0.00001 93 NBNC-HCC versus BC-HCC 4 [ 9 , 11 , 24 , 29 ] 213 -29.3...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the clinicopathological characteristics and prognosis of patients with NBNC-HCC following hepatectomy. The characteristic features of patients with NBNC-HCC are older age (similar to those with HCV-HCC), increased incidence of hypertension, DM, heavy alcohol consumption, and large tumors, and a reduced incidence of liver cirrhosis (21)(22)(23)(24). In the current study, similar characteristics were revealed; in particular, the NBNC group patients had significantly lower serum albumin values than the HBV group patients and higher serum albumin values than the HCV group patients, despite a significantly lower incidence of liver cirrhosis in the NBNC group than the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the measurement of both AFP and DCP has been strongly recommended in the Clinical Practice Guidelines for Hepatocellular Carcinoma ( 14 reported to have relatively low serum AFP levels compared to hepatitis B-derived HCCs (15). Also, hepatitis C-infected livers usually have high serum AFP levels (16).…”
Section: Discussionmentioning
confidence: 99%